Evaluasi Kinerja Industri Jasa Otomotif Melalui Strategi Balanced Scorecard - Muhammad Farid (Industrial Engineering Study Program, Pattimura University, 2010)
Performance appraisal system is needed is a system that can assess the performance of all key components in the company. Balanced scorecard became one of the methods used to evaluate the performance of an enterprise in a comprehensive manner. Automotive service industry in particular workshop are included in general requires a qualified repair shop performance improvement strategy feasible, using the balance scorecard is expected to contribute through four perspectives: 1) financial, 2) customer, 3) internal business processes, 4) learning and growth..